2021
DOI: 10.1021/acssuschemeng.1c05352
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Atomically Dispersed Co–Nx Sites Anchored on Ultrathin N-Doped Carbon Nanosheets with Durability Oxygen Reduction Reaction of Zinc–Air Batteries

Abstract: Highly efficient and low-cost oxygen reduction reaction electrocatalysts play key roles in the development of advanced energy conversion and storage devices, such as fuel cells and metal–air batteries. Herein, a facile strategy of synthesizing cobalt single atoms anchored on an ultrathin N-doped carbon nanosheet electrocatalyst (marked as CoSAs/N-CNS) via an in situ g-C3N4 template strategy was reported. Impressively, benefiting from highly active Co–Nx sites and highly porous and ultrathin nanosheet morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In addition, the LSV curves of 2D NiCo-61-MOF at different rotation rates are shown in Figure S6. It could be obviously observed that with the rotation rate increasing, the current density had no obvious change, and the I –1 hardly changed with the change of ω –1 , which confirmed that the EBO was mainly dependent on the electrode kinetics. , These results suggested that Ni sites may present higher activity than the Co site in 2D MOF, which significantly contributed to the kinetics current. The Co 2+ -added optimized electron structure showed a highly active Ni site.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the LSV curves of 2D NiCo-61-MOF at different rotation rates are shown in Figure S6. It could be obviously observed that with the rotation rate increasing, the current density had no obvious change, and the I –1 hardly changed with the change of ω –1 , which confirmed that the EBO was mainly dependent on the electrode kinetics. , These results suggested that Ni sites may present higher activity than the Co site in 2D MOF, which significantly contributed to the kinetics current. The Co 2+ -added optimized electron structure showed a highly active Ni site.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of isolated cobalt atoms in N-CNs signicantly improved the catalytic activity with an E 1/2 of 0.91 V and stability up to 67 h compared to NCNs by lowering the E a of the RDS to 0.32 V compared to N-CNS. 102 Xiaojuan Liu and co-workers synthesized a uniformly distributed cobalt single-atom catalyst embedded into hollow carbon spheres. The catalyst exhibited outstanding and improved activity compared to the conventional CoSAs.…”
Section: Single-atom Catalystsmentioning
confidence: 99%
“…The incorporation of isolated cobalt atoms in N-CNs significantly improved the catalytic activity with an E 1/2 of 0.91 V and stability up to 67 h compared to NCNs by lowering the E a of the RDS to 0.32 V compared to N-CNS. 102…”
Section: Fundamentals Of the Orrmentioning
confidence: 99%
“…This substrate has a high degree of graphitization, a loose porous structure, and abundant edges, which are conducive to the formation of a large number of active sites and mass transport/electron transfer. 115 Fe 1 /d-CN has been obtained by growing another layer of Fe-containing ZIF-8 outside the ZIF-8, followed by pyrolysis. A higher I D / I G value indicates more defects in Fe 1 /d-CN.…”
Section: Factors Affecting the Orr Performances Of Npt-sacsmentioning
confidence: 99%